2014
DOI: 10.1186/1475-2859-13-16
|View full text |Cite
|
Sign up to set email alerts
|

Transcription analysis of recombinant industrial and laboratory Saccharomyces cerevisiae strains reveals the molecular basis for fermentation of glucose and xylose

Abstract: BackgroundThere has been much research on the bioconversion of xylose found in lignocellulosic biomass to ethanol by genetically engineered Saccharomyces cerevisiae. However, the rate of ethanol production from xylose in these xylose-utilizing yeast strains is quite low compared to their glucose fermentation. In this study, two diploid xylose-utilizing S. cerevisiae strains, the industrial strain MA-R4 and the laboratory strain MA-B4, were employed to investigate the differences between anaerobic fermentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 96 publications
7
64
3
Order By: Relevance
“…This is in accordance with the previous observation of partial CCR in xylose-grown S. cerevisiae under anaerobiosis by Runquist et al (2009). The observed higher expression levels of gluconeogenetic FBP1 and PCK1 in S. cerevisiae during anaerobic growth on xylose compared to growth on glucose are consistent with a number of previous observations (Wahlbom et al 2003;Jin et al 2004;Salusjärvi et al 2008;Matsushika et al 2014). Accordingly, TDH1 and GPM2 have been found more highly expressed during xylose dissimilation (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with the previous observation of partial CCR in xylose-grown S. cerevisiae under anaerobiosis by Runquist et al (2009). The observed higher expression levels of gluconeogenetic FBP1 and PCK1 in S. cerevisiae during anaerobic growth on xylose compared to growth on glucose are consistent with a number of previous observations (Wahlbom et al 2003;Jin et al 2004;Salusjärvi et al 2008;Matsushika et al 2014). Accordingly, TDH1 and GPM2 have been found more highly expressed during xylose dissimilation (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…at 24.5 h in mixed glucose-xylose cultures) compared to catabolism of glucose (i.e. at 6.5 h in the glucose cultures), as previously reported (Runquist et al 2009;Matsushika et al 2014). TDH1 encodes a glyceraldehyde 3-phosphate dehydrogenase isoform, which is responsive to NADH stress (Valadi et al 2004), and downregulated in evolved strains as a consequence of improved xylose utilisation (Karhumaa et al 2009;Linck et al 2014).…”
Section: Discussionmentioning
confidence: 89%
“…Cat8 and Hap4 are respiratory factors active in the general cellular response to xylose, and deletion of HAP4 was recently shown to improve cellobiose consumption rates (28,30). MSN2 and MSN4, encoding stress-associated factors, were observed to be highly up-regulated in xylose and their transcriptional targets misregulated (31). ADR1 is an activator of ADH2, a glucoserepressed gene that encodes an alcohol dehydrogenase that catalyzes a key step in ethanol consumption (32,33).…”
Section: −5mentioning
confidence: 99%
“…Another study found that xylose also acts as a weakly repressive carbon source, less strongly than glucose [7,8]. In addition, transcript levels of HAP4, which encode a transcriptional activator and global regulator of respiratory gene expression [9], were induced manyfold in the presence of xylose compared to induction in the presence of glucose [5,6]. Thus, S. cerevisiae engineered for xylose metabolism does not exhibit a fermentative response to xylose even under anaerobic conditions, and the regulation of xylose metabolism in recombinant S. cerevisiae is similar to glucose metabolism in Crabtree-negative yeast [10].…”
mentioning
confidence: 95%
“…Investigations using genome-wide transcription analysis have suggested that xylose-utilizing S. cerevisiae strains recognize xylose as a non-fermentable carbon source [5,6]. Another study found that xylose also acts as a weakly repressive carbon source, less strongly than glucose [7,8].…”
mentioning
confidence: 97%